Fusing rigid planar units to engineer twisting molecules as dual-state emitters. (13th April 2022) - Yin, Yuanye; Ding, Aixiang; Yang, Longmei; Kong, Lin; Yang, Jiaxiang
Abstract : The fusion of multiple rigid, planar units into a highly twisting molecule is proposed as a molecular engineering strategy for synthesizing bright dual-state emitters. Applications such as mechanosensor and fluorescent probe have been demonstrated. Abstract : Leveraging dual-state emitters (DSEgens) to achieve intense emission in both dilute solutions and the solid state is rapidly emerging as a trending research spot in the field of luminescent materials as these materials have found wide applications in dual states. Despite the advance in materials and applications, it is still challenging to obtain a DSEgen through a rational molecule design. Herein, we propose a molecular engineering strategy to afford two arylimidazole emitters, NIFBCZ and NIBBCZ, as DSEgens with highly twisting conformation by fusing multiple rigid, planar units into a molecule. NIFBCZ and NIBBCZ have high emission quantum yields (QYs) of 52.3% and 62.7% in THF solution and 42.5% and 62.4% in the solid state. Single crystal X-ray diffraction study and theoretical calculation reveal that the highly twisting conformation, the presence of multi-intramolecular weak interactions, and effective intramolecular charge transfer (ICT) play key roles in the dual-state emission. With the two DSEgens, clear mechanochromism, specific recognition of picric acid (PA) over various nitroaromatic compounds (NACs), and trace water detection in organic solvents were demonstrated. The detection limits are 97 nM (PA) and 0.0010% (water) for NIFBCZ and 180 nM (PA) and 0.0027% (water) for NIBBCZ . Of particular note, the higher QY of NIFBCZ in comparison with that of NIBBCZ could stem from its enhanced local rigidity and planarity by the coupling of the two phenyl pendants in the arylimidazole core, suggesting the active role of local rigidification in improving the photophysical properties. The new molecular engineering strategy in this study provides a new paradigm for the design of DSEgens.